Consecutive Conflicting Jurisdiction Agreements under the Brussels Ibis Regulation. Comment on the Austrian Oberster Gerichtshof’s ruling of 23 September 2024 (case 7 Ob 116/24w) - Rademacher, Lukas (CUADERNOS DE DERECHO TRANSNACIONAL, 2025)
Surprisingly, the recently published report by the European Commission on the Brussels Ibis Regulation does not take into consideration a reform of Art. 25(1). The application of the provision continues to pose challenges for the courts of the Member States. A recent decision by the Austrian Oberster Gerichtshof provides another example. The court was confronted with consecutive conflicting jurisdiction agreements. Instead of referring the resulting questions to the CJEU, the court concluded that the agreements cancelled each other out and that the competent court should be determined by applying the general rules on international jurisdiction (Arts. 4(1), 63(1) lit. a Brussels Ibis Regulation). It is submitted that the court was correct to apply autonomous European standards when assessing the parties’ agreements. However, such standards have yet to be established by the CJEU. The Austrian court’s reasoning does not seem convincing.
Keywords: international jurisdiction; jurisdiction agreement; interpretation; invalidity; Brussels Ibis Regulation